1997
DOI: 10.1148/radiology.204.2.9240546
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal tumor: MR imaging with dilute oral barium and intravenous gadolinium-containing contrast agents compared with unenhanced MR imaging and CT.

Abstract: Double-contrast MR imaging demonstrated more peritoneal tumors than CT or unenhanced spin-echo MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
75
1
8

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(86 citation statements)
references
References 0 publications
1
75
1
8
Order By: Relevance
“…MRI is comparable to CT in several aspects, in detecting deposits of more than 1 cm [18]. The use of fat suppression, delayed post contrast enhancement and water soluble enteric contrast have allowed detection sensitivities to surpass CT [20] Peritoneal enhancement more than liver enhancement is abnormal and is visualised due to the superior contrast resolution-a sign that may not be readily appreciated on MDCT. [18] MRI is more sensitive that CT for subcentimetric sized deposits and also in anatomically difficult sites (e.g.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…MRI is comparable to CT in several aspects, in detecting deposits of more than 1 cm [18]. The use of fat suppression, delayed post contrast enhancement and water soluble enteric contrast have allowed detection sensitivities to surpass CT [20] Peritoneal enhancement more than liver enhancement is abnormal and is visualised due to the superior contrast resolution-a sign that may not be readily appreciated on MDCT. [18] MRI is more sensitive that CT for subcentimetric sized deposits and also in anatomically difficult sites (e.g.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…Some studies have demonstrated improved lesion detection with magnetic resonance imaging (MRI) [16,17], but not all [18].…”
Section: Diagnosis Of Colorectal Cancer Peritoneal Carcinomatosismentioning
confidence: 99%
“…Recent developments in patient treatment include total peritonectomy and multivisceral resection of all involved tissue combined with hyperthermic intraperitoneal chemotherapy (HIPEC) as an approach with curative intention [4 -6]. Several imaging modalities are used in the preoperative assessment of tumor extent including ultrasound [7], computed tomography (CT) [8,9], magnetic resonance imaging (MRI) [10,11] as well as F-18-FDG positron emission tomography/computed tomography (PET/CT) [9, 12,13]. Recent studies indicate good results especially for MRI and PET/CT due to its potential of functional and morphological tissue characterization [10,11].…”
mentioning
confidence: 99%
“…Several imaging modalities are used in the preoperative assessment of tumor extent including ultrasound [7], computed tomography (CT) [8,9], magnetic resonance imaging (MRI) [10,11] as well as F-18-FDG positron emission tomography/computed tomography (PET/CT) [9, 12,13]. Recent studies indicate good results especially for MRI and PET/CT due to its potential of functional and morphological tissue characterization [10,11]. The assessment of recurring PC after HIPEC is even more challenging than the preoperative evaluation as peritonectomy and HIPEC come along with extensive postoperative tissue alterations often accompanied by inflammatory reaction after HIPEC.…”
mentioning
confidence: 99%